Surgical treatment of cystic neoplasms of the pancreas - Coelho,Júlio Cezar Uili (2010)
CONTEXT: Diagnosis and treatment of cystic neoplasms of the pancreas increased significantly in the last decades. There are only a few Brazilian publications on these tumors. The majority of them are limited to reports of one or few cases. OBJECTIVE: To present our experience with 27 patients with cystic neoplasms of the pancreas. METHODS: Demographic data, clinical manifestations, diagnostic exams, surgical procedures, postoperative complications, and follow-up data of 27 patients with cystic neoplasms of the pancreas were analyzed, according to the histological type of the tumor. RESULTS: There were 10 (37%) serous cystic tumors, 10 (37%) mucinous cystic tumors, 4 (15%) intraductal papillary mucinous tumors, and 3 (11%) solid pseudopapillary tumors or Frantz tumor. All serous cystic tumors, 6 (60%) mucinous tumors, 2 (50%) intraductal papillary mucinous tumors, and 2 (67%) solid pseudopapillary tumors were benign. The age of the patients varied from 31 to 82 years and all tumors were more common in female. Two patients had been treated previously as a pseudocyst. Surgical procedures depended on the location and extension of the tumor. Two patients underwent only laparotomy with tumor biopsy, one cholecystectomy with Roux-en-Y hepaticojejunostomy for jaundice treatment, 6 pancreatoduodenectomy, and 18 partial pancreatectomy. The most common postoperative complication was pancreatic fistula (n = 5; 19%). One patient died of necrotic pancreatitis. Of the 10 patients with serous cystic tumor, only 1 had tumor recurrence at the section border. The three patients with mucinous cystoadenocarcinoma in which was not possible to resect the tumor, died 6 to 24 months after laparotomy. The six patients with benign mucinous tumors did not have tumor recurrence. CONCLUSIONS: The most common cystic neoplasms of the pancreas are serous and mucinous cysts. These tumors are more frequent in female. Although almost all serous cysts are benign, 40% of mucinous cysts are malign. Misdiagnosis may delay appropriate treatment and increase mortality.